Distribution of Diaphorina citri Kuwayama (Hemiptera: Liviidae) in citrus production areas of Panama - Atencio-Valdespino, Randy (2023)
Introduction. The asian psyllid (Diaphorina citri Kuwayama) is the main vector of the bacterium Candidatus Liberibacter asiaticus that causes Huanglongbing (HLB) disease in citrus in Panama. Objective. To determine the geographic distribution and host plants of the asian psyllid within the citrus growing areas in Panama. Materials and methods. The study was carried out from June to October 2021 through systematic sampling within 46 localities associated with commercial citrus and home gardens in seven provinces of Panama. In each plant, two new shoots of 10 cm long were bagged with a magic-seal plastic bag to capture the specimens and introduce them into 2 mm plastic vials with 95 % alcohol for later identification. The study variable included the count of the total number of specimens, and the data was analyzed as a percentage. Results. Of the total of 73 collected samples, the presence of the Asian psyllid was confirmed in 21.92 % (16 samples). Its presence was positive in the provinces of Chiriquí, Coclé, Herrera, Panama, and West Panama, at altitudes of 17 to 1080 m.a.s.l. There was no presence of the psyllid in the provinces of Los Santos and Veraguas. Of the 16 samples that were positive, 50 % belonged to the myrtle plant, followed by orange (18.75%), and creole lemon (12.50 %). Conclusion. The distribution of the asian psyllid vector of HLB in commercial citrus and home gardens in the main citrus growing areas in Panama was presented at different heights above sea level, mainly associated with the presence of the host plants such as myrtle, orange, and creole lemon.